THE ROLE OF THE TECTONICS AND HYDROGEOLOGY AT THE TSAKONA (ARKADIA, PELOPONNESE, GREECE ) LANDSLIDE - Φουντούλης, I.; Λαδάς, I.; Σπυρίδωνος, E.; Μαριολάκος, Η. (Bulletin of the Geological Society of Greece, 2004)
The present paper aims to the understanding of the causes of the large-scale landslide that occurred at Tsakona area (SW Arcadia, Peloponnesus) during February 2003. This is the largest landslide that have ever effected the Greek National highway network as it entirely rubed out the new Megalopolis-Kalamata highway at a length of 200m. It took place at the western slopes of Drosovouni Mt., which exhibits an elogated shape of NE-SW direction. At the broader area of the slide three alpine formations of the Pindos unit occur which from lower to upper are: (i) the Jurassic radiolarites, (ii) the so called 1s t flysch and (iii) the Upper-Cretaceous pelagic limestones. The initial sliding took place inside the first two formations and the landslide moved more than 1,000 meters downward along the mountain slope at an E-W direction while its headscarp was near the tectonic contact between these formations and the upperlying pelagic limestones. In order to understand the causes of the landslide we carried out a detailed geological, morphotectonic, microtectonic and neotectonic study of the broader area. Additionally we constructed the structural contour map between the limestones nappe and the underlying formations. From all the aforementioned we suggested that the landslide occurred in a tectonically active area where the neotectonic deformation. Based on the above-mentioned studies, we have to mention the followings: The landslides occur in a site that the tectonic deformation is very intense. There were old landslides before the activation of the last one and before the study and construction of the highway. The constructors as well as the people that studied the area did not take into account the already existed landslides. It has to be mentioned that hydrogeological regime of the area is of great importance, as to the opposite slopes of the landslide in which occur the same formations like in the landslide area there is no landslide activity at least the last 100 years as indicated by the existing railway, due to the no occurrence of limestones above the radiolarites. From all the above mentioned it is clear that the tectonics - neotectonics affected the major area are the main factors involved to the initiation of the landslide, and the crossing of the landslide by the highway contributed to the reactivation together with the rains.